Village level inequality, migration and remittances in rural Mexico: How do they change over time? - Aslıhan Arslan; J. Edward Taylor (Kiel Institute for the World Economy (IfW), 2010)
We analyze how migration prevalence and remittances shape income distribution using novel panel data that is nationally and regionally representative of rural Mexico. Employing a Gini decomposition and controlling for whole household migration (attrition), we find that migration prevalence has increased between 2002 and 2007 reversing the unequalizing effects of international remittances at the national level. We also analyze regional differences in the effects of remittances on inequality, and find that the regions that had the highest increase in international migration are also the regions where the equalizing change in the marginal effects of remittances was the highest. This provides supporting evidence for the migration diffusion hypothesis. A fixed effects analysis of the effects of migration and remittances on in inequality at the village level, however, fails to support this hypothesis, indicating that most changes in inequality have occurred within rather than between villages. We show that income growth has been pro-poor in all villages, but this is offset by significant re-ranking of individuals in the village inequality measure, concealing the effects of migration and remittances on income distribution at the village level.
Keywords: O15; 330; Inequality; Migration; Network effects; Panel data; Remittances; Mexico; Ländliche Einkommensverteilung; Rücküberweisung (Migranten); Migranten; Soziales Netzwerk; Schätzung; Mexiko